ANALISIS RETRIBUSI EKOWISATA MANGROVE PANGKAL BABU TERHADAP PENDAPATAN ASLI DAERAH SEKTOR PARIWISATA KABUPATEN TANJUNG JABUNG BARAT - -, Raisha az zahra; Siti Hodijah; Rahma Nurjanah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to determine and analyze the development and contribution of Pangkal Babu mangrove ecotourism levies to the Regional Original Income of the Tourism Sector and the total PAD of West Tanjung Jabung Regency. The data used are secondary data in the form of mangrove levy revenue data and West Tanjung Jabung Regency PAD data for 2023-2025 obtained directly from the Department of Tourism, Youth and Sports (Disparpora) and the Regional Development Planning Agency (Bappenda) of West Tanjung Jabung Regency. The method used is descriptive qualitative with development and contribution analysis. The results of this study indicate that the development and contribution of mangrove ecotourism fluctuate from year to year, with an average development of 16.62%, an average contribution to tourism PAD of 48% and an average contribution to the total PAD of West Tanjung Jabung of 0.00264%.